Interactions of Neisseria meningitidis with the human immune system - Harding, R (2015)
Neisseria meningitidis is an obligate human pathogen causing over 1000 cases of meningococcal disease within the U.K., 10 % of which result in long-term disability or fatality. 10-70 % of the population carry N. meningitidis in their nasopharynx, the natural reservoir of this bacterium, as a commensal. The host-pathogen interactions of this species are complex and a greater understanding of the molecular mechanisms involved in pathogenesis and immune evasion is required. Three aspects of N. meningitidis pathogenesis were explored in this study. One mechanism of immune evasion which promotes serum resistance of N. meningitidis is recuitment of complement factor H through domains 6 and 7 (fH67) by factor H binding protein (fHbp). In this study, mouse fH67 was recombinantly expressed and purified. fHbp did not bind mouse fH67 at physiologically relevant protein concentrations. The structure of mouse fH67 was solved, showing differences in domain orientation and surface chemistry compared to the human version of this protein, potentially accounting for the host specificity of this interaction. Type IV pili (T4P) are crucial adhesins of N. meningitidis, the fibre of which is composed of thousands of copies of PilE. A method was developed to recombinantly produce large quantities of this protein from a variety of meningococcal strains and the structure was solved of one PilE protein. Subsequent analysis was performed with the PilE proteins investigating their interaction with the putative pilus receptor CD46 and human epithelia as well as their immunogenicity. A method was also established to produce PilC, the proposed tip-assocoated adhesin of T4P. ZapE has recently been identified as an important protein in pathogen colonisation, functioning as an ATPase linked to Z-ring formation in bacterial cell fission. Both N. meningitidis and E. coli ZapE were recombinantly produced. The domain boundaries were mapped and ATPase activity was confirmed. No interaction was seen with FtsZ but DNA binding and modulation was observed by shift assays, the exact function of which remains to be elucidated in future studies.